Empirical Study on Psychological Capital of Employees in Supply Chain Enterprises at Shenzhen in China - Kian Aun Law; Valliappan Raju; Amiya Bhaumik (International Journal of Supply Chain Management, 2019)
This study focuses on the relationship between psychological capital structure, psychological capital and related factors of Shenzhen Supply Chain enterprises employees. Shenzhen Supply Chain enterprises stand in the front line of China's developed regions, which is the vane of the local economy. The acquisition and maintenance of their competitive advantages is a subject that corporate managers, academic researchers who care about corporate management and even government departments should be faced. People have to pay attention to the positive and developmental psychological elements that employees exhibit in the working environment, growth and development process. This psychological factor has input-output characteristics, which is conducive to the improvement of individual work performance and meets the Psychological Resources criteria for active organizational behavior. Thereby helping companies gain new competitive advantages. On the basis of literature research, this study collected 1768 psychological capital initial response items from 392 technicians in Shenzhen Province through personal interviews, group interviews and questionnaires. Concluded 35 initial psychological capitals from behavioral events. In terms of Entries, 92 initial capital entries were obtained through content analysis. A psychological capital pre-test questionnaire was compiled, and 254 valid responses for Shenzhen Supply Chain employees were collected. On this basis, researchers used strict item screening procedures and project analysis methods, EFA, CFA and other quantitative means, innovatively obtained the high-level structure of five-dimensional psychological capital which is Hope, Optimism, Resilience, Authenticity and Forgiveness of the employees in Shenzhen Supply Chain enterprises. After using correlation analysis, regression analysis, exploratory factor analysis, confirmatory factor analysis and other statistical methods, and using triangulating Excel, SPSS, AMOS and other statistical tools, researchers focus on the analysis and verification of the research models and related hypotheses proposed in this study. Innovatively analyzed the multiple mediating role of psychological capital in organizational support and emotional commitment, work input, and job performance, and provides important research conclusions for academic circles and management practices. Finally, the paper summarizes the conclusions of this study, and explains the limitations and shortcomings in the research, as well as the prospects of subsequent research.